PERAN HARGA DALAM MEMPENGARUHI MINAT PEMBELIAN KEBAYA DI BUTIK IMAS COLLECTION - Febriyanti, Rika; Ambarita, Inka Fiorentina; Putri, Yoshi Malika; Rofiudin, Muhamad Yusuf; Madika, Gilang Vahera; Wiharso, Gani (LPPM Universitas Nusa Mandiri, 2024)
The fashion industry in Indonesia continues to experience rapid growth, with traditional clothing such as kebaya gaining increasing popularity. Price is one of the key factors influencing consumer interest, particularly in niche markets like kebaya boutiques. This study aims to evaluate the role of price in influencing consumer purchase interest through a case study at Butik Imas Collection. A qualitative approach was used with a case study method, involving in-depth interviews with the boutique owner and 10 female consumers, as well as direct field observations. The findings reveal that although price is a significant factor, consumers also consider other aspects such as fabric quality, kebaya design, and customer service. These findings support the price perception theory by Kotler and Armstrong and align with previous research by Sawitri et al. (2024), which states that the combined application of price and product quality can enhance purchasing decisions. This study provides strategic insights for boutique managers on the importance of maintaining competitive pricing without compromising quality. A combination of competitive pricing, superior product quality, and excellent customer service can boost consumer purchase interest while strengthening Butik Imas Collection's position in the kebaya market.